Florida palms : a novel - Pan, Joe (Simon & Schuster, 2025)
"All they wanted was a summer job, a way to make a little cash. Three broke Florida boys, fresh out of high school and wild at heart, get hired by a moving company run by one of their fathers: a gruff, felonious old Hells Angels biker who has supposedly retired from the fast life. But when a stranger from the father's past rolls into town, the boys' small world gets flipped upside down. They discover that the moving company is a front for a criminal organization shipping a new designer drug up the East Coast. Enticed by larger pay checks and fueled by burgeoning drug habits, the young friends soon find themselves mixed up with rank opportunists, meth zombies, killer cops, and a panther-hunting hitman, each fighting it out for a shot at the Big Time. Will the young men find redemption, or will they end up like so many others, lying face down in the muck of the unforgiving swamps?"--